Analysis Of The World Trade Organization Panel Decision Between Indonesia And The European Union In Case Number Ds592 Of 2022 Concerning Restrictions On Exports Of Low-Grade Nickel Ore - Zampara Mernissi; Risnain, Muh; Pitaloka, Diva (Mataram Journal of International Law, 2023)
The purpose of this study is to analyse the suitability of Indonesia's nickel export restriction policy to international trade rules at the WTO and analyse the actions taken by the Indonesian Government following the WTO Panel Decision regarding the nickel export restriction policy. The research method uses the normative-legal research method. The legal approach methods use statutes, cases, international agreements, and conceptual approaches. The legal material sources or types of legal materials use primary and secondary legal materials. The legal material collection technique used is library data. The analysis of legal materials used is a review of statutory regulations and international agreements. The result of the study showed that the panel has decided that Indonesia has violated Article XI:1 GATT 1994 so Indonesia's policy cannot be justified by Articles XI:2 (a) and XX GATT 1994. Indonesia finally appealed the WTO Panel Report Number DS592. Researchers recommend considering the use of the Principles of Permanent Sovereignty over Natural Resources and Special and Different Treatment as a defence for the Indonesian Government. Furthermore, Indonesia can connect the policy of limiting nickel ore exports to the Net Zero Emission’s mission. Retaliation against the EU could be an alternative solution, but with the caveat that the Indonesian Government must ensure that the retaliation is right on target and does not harm the country's economy and the country's politics.